2015
DOI: 10.24925/turjaf.v3i11.891-893.385
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cooking on Quality Commonly Consumed Marine Fish Platycephalidae (Platycephalus indicus) in Iran

Abstract: Fish Platycephalus indicus usually are consumed by southern people in Iran. The present study assessed the effect of processing on proximate compositions in the fillets of P.indicus. The fish samples were prepared by boiling, baking and frying, while proximate analysis was done by standard methods. Boiling processing method significantly reduced ash content in the fillet whereas fat content was significantly increased in frying. Baking method recorded highest ash content of 10.64%. The highest protein concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Some evidence is contradicting, so it is important to consider several factors when looking at results. In terms of microwaving and grilling, this has increased greatly in recent years and is not as harsh as it once was, thus outdating some of the previous studies conducted decades ago [ 227 ]. Moreover, some studies reported large changes to the PUFA and SFA as well as n-6/n-3 PUFA ratios after thermal processing and cooking, which contradicts other studies that have failed to see any major effects of the different cooking methods on fish fatty acid composition [ 228 ].…”
Section: The Effects Of Thermal Processing—cooking On the Bio-functio...mentioning
confidence: 99%
“…Some evidence is contradicting, so it is important to consider several factors when looking at results. In terms of microwaving and grilling, this has increased greatly in recent years and is not as harsh as it once was, thus outdating some of the previous studies conducted decades ago [ 227 ]. Moreover, some studies reported large changes to the PUFA and SFA as well as n-6/n-3 PUFA ratios after thermal processing and cooking, which contradicts other studies that have failed to see any major effects of the different cooking methods on fish fatty acid composition [ 228 ].…”
Section: The Effects Of Thermal Processing—cooking On the Bio-functio...mentioning
confidence: 99%
“…This high protein in fried fish was also reported by Aberoumand and Ziaei Nejad. 22 It is clear that protein decreased in the frozen samples. In this study, frozen storage reduced the protein content in frozen fish.…”
Section: Resultsmentioning
confidence: 97%
“…Kandungan abu dalam suatu bahan pangan dapat menunjukkan kandungan mineral di dalamnya (Kasim et al, 2018). Peningkatan kadar abu disebabkan oleh adanya penurunan kandungan air dalam snack bar yang dapat meningkatkan kadar abu (Aberoumand & Ziaei-nejad, 2015;Sarastuti & Yuwono, 2015). Hasil analisis menunjukkan bahwa kandungan abu tertinggi adalah snack bar F3 dengan perbandingan pisang raja dan kedelai 70:30, yaitu sebesar 4,02 g. Hal ini disebabkan oleh semakin tinggi konsentrasi kedelai, maka semakin tinggi kandungan kalsium dalam snack bar, dimana dalam 100 g kedelai mengandung 222 mg kalsium, sehingga kadar abu juga semakin meningkat (Waspadji et al, 2010).…”
Section: Analisis Dataunclassified